2014
DOI: 10.4172/2329-9096.1000248
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Skeletal Muscle MR Imaging Approaches in the Assessment of Muscular Dystrophies

Abstract: Muscular dystrophies (MDs) are inherited diseases that lead to progressive skeletal muscle weakness and functional decline. Currently, the diagnosis is generally made on clinical grounds and confirmed by genetic testing, serologic assessments, neurophysiologic measurements or muscle biopsy. Given our understanding of the pathophysiology of these dystrophies, advancements in magnetic resonance imaging (MRI) techniques may assist clinicians in identification and monitoring of skeletal muscle disease progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…Recent advancements in quantitative MRI have significantly expanded the potential to evaluate pathologic changes in muscle disorders, including composition, architecture, mechanical properties, perfusion, and function. [1][2][3][4][5] Semi-quantitative methods can assess and grade the extension of compositional changes such as fatty degeneration. 1 Moreover, it has been shown that T 1 relaxation significantly decreased with fat infiltration and increased with edema.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in quantitative MRI have significantly expanded the potential to evaluate pathologic changes in muscle disorders, including composition, architecture, mechanical properties, perfusion, and function. [1][2][3][4][5] Semi-quantitative methods can assess and grade the extension of compositional changes such as fatty degeneration. 1 Moreover, it has been shown that T 1 relaxation significantly decreased with fat infiltration and increased with edema.…”
Section: Introductionmentioning
confidence: 99%
“…Such techniques can effectively provide information beyond what can be seen and assessed at conventional MRI; their development and application in clinical practice can play an important role in defining the disease course and treatment response (2730).…”
Section: Applications Of Advanced Quantitative Techniquesmentioning
confidence: 99%
“…Currently, the diagnosis is generally made on clinical grounds and confirmed by genetic testing, serologic assessments, neurophysiologic measurements, or muscle biopsy [3]. Dystrophic changes in affected muscles usually do not occur randomly but rather develop in a specific pattern [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, their use may be limited in the assessment of disease status in muscle dystrophies (MDs), especially because young children are commonly affected and repeated evaluations are necessary due to the tendency of muscles to degenerate over time. An imaging approach is desired in this case [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation